INDIVIDUAL CHARACTERISTICS IN PATH-GOAL THEORY TO INCREASE PRODUCTIVITY - Sutianingsih, Sutianingsih; Handayani, Rini (Faculty of Economic and Business, University of Pasundan, 2023)
This research was motivated by the low productivity of small industries. The main objective of this study is to develop research concepts related to path-goal theory and empirical research models to fill research gaps on the effect of workability and work experience on productivity.This research is critical to achieving expected productivity through increased capabilities, work experience, and innovation. Respondents were small snack entrepreneurs, and data analysis with regression.The findings of this study are that work ability, work experience, and innovation significantly affect productivity. Innovation cannot strengthen the effect of workability on productivity, but it can enhance the influence of work experience on productivity.The novelty of this research is the development of path-goal theory, which that work ability and work experience can be used as dependent variables that can affect productivity.